The Influence of Caesarean Section Education Program and Quranic Recitation Therapy on Anxiety Levels in Preoperative Patients at RA Kartini Hospital, Jepara Regency - Imam Subhi; Irwan Budiono; Yuni Wijayanti (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: This study was conducted to analyze theeffect of sectio caesarea program education and qur'an murrotal therapy on reducing anxiety levels in sectio Caesarea pre-operative patients at RA Kartini Hospital, Jepara Regency. Methods: The design of this study used a quasi-experimental non-randomized pretrial post-test control design, the minimum number of samples used in this study was 40 patients for 20 samples of educational program interventions and murrotal therapy and 20 samples of control samples. Results: The results of the analysis based on the measurement time showed that the pretest value in both the intervention group and the control group showed no significant difference with a p-value of 0.573 meaning that both groups of respondents had the same level of anxiety before the intervention. Meanwhile, the posttest value showed that there were significant differences in the two groups after the intervention in the intervention group showed a higher decrease in anxiety level than the control group with a p-value of < 0.05.